Immediate Effects of Bilateral Neuromuscular Taping on Upper Trapezius Muscle in Patients with Chronic Mechanical Neck Pain: A Randomized Clinical Trial - Sanchez-Jorge, Sandra; Pascual-Vaca, Angel Oliva; Rodriguez-Lopez, Elena Sonsoles; Valera-Calero, Juan Antonio (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Background Researchers investigated the effects of neuromuscular taping on different musculoskeletal conditions. Considering the demonstrated short-term effectiveness of neuromuscular taping for the management of shoulder pain, kinesiotaping may also be beneficial in reducing pain in patients with chronic mechanical neck pain.Objective To determine the immediate effects of neuromuscular taping on head position, neck pain and cervical range of motion in individuals with neck pain. Methods Sixty subjects with chronic neck pain were randomly assigned to 1 of 2 groups: the experimental group received neuromuscular taping on upper trapezius bilaterally (with tension) and the placebo group received a sham neuromuscular taping application (without tension). Visual analogue scale (VAS), craniocervical angle and cervical range of motion data were collected at baseline and immediately after the neuromuscular taping application.Results The group-by-time interaction for t-test was statistically significant for pain recorded by visual analogue scale (p< 0.001). Patients in the experimental group obtained a similar improvement in pain to those in the control group (p< 0.001).Conclusions Patients with mechanical neck pain who received and application of neuromuscular taping with proper tension or sham neuromuscular taping exhibited similar reductions in neck pain intensity, but not in cervical range of motion.Hintergrund Die Forscher untersuchten die Auswirkungen von neuromuskulärem Taping auf verschiedene Erkrankungen des Bewegungsapparates. In Anbetracht der nachgewiesenen kurzfristigen Wirksamkeit von neuromuskulärem Taping bei der Behandlung von Schulterschmerzen kann Kinesiotaping auch bei Patienten mit chronischen mechanischen Nackenschmerzen zur Schmerzreduktion beitragen.Ziel Ermittlung der unmittelbaren Auswirkungen von neuromuskulärem Taping auf die Kopfposition, die Nackenschmerzen und den Bewegungsumfang des Halses bei Personen mit Nackenschmerzen.Methoden 60 Probanden mit chronischen Nackenschmerzen wurden zufällig einer von 2 Gruppen zugeordnet: Die Versuchsgruppe erhielt bilateral (unter Spannung) ein neuromuskuläres Taping am oberen Trapezius und die Placebogruppe erhielt ein scheinbares neuromuskuläres Taping (ohne Spannung). Die visuelle Analogskala (VAS), der kraniozervikale Winkel und der zervikale Bewegungsumfang wurden zu Beginn und unmittelbar nach der Anwendung des neuromuskulären Tapings erfasst.Ergebnisse Die Wechselwirkung nach Zeitgruppen für den t-Test war für die mit der visuellen Analogskala aufgezeichneten Schmerzen statistisch signifikant (p <0,001). Patienten in der Versuchsgruppe erzielten eine ähnliche Schmerzverbesserung wie Patienten in der Kontrollgruppe (p <0,001).Schlussfolgerungen Patienten mit mechanischen Nackenschmerzen, die neuromuskuläres Taping mit angemessener Spannung erhalten und angewendet haben, zeigten eine ähnliche Verringerung der Intensität der Nackenschmerzen, jedoch keine Verringerung im Bewegungsumfangs des Halses
Keywords: musculoskeletal diseases; physical therapies; pain